Ferromagnetism in the filled beta-Mn phase Fe2-xRhxMo3N - Oldham, SE; Battle, P; Blundell, S; Brooks, M; Pratt, F; Prior, T (2005)
Compositions in the solid solution Fe2-xRhxMo 3N which adopt the filled β-manganese structure have been prepared by the reductive nitridation of mixed binary metal oxides; single-phase samples can be prepared for 0.3 ≤ x ≤ 0.75. Those compositions with x ≤ 1 have been shown, by a combination of magnetometry, neutron diffraction and μSR, to be ferromagnetic at low temperatures. The Curie temperature is highest (Tc = 110 K) for x = 0.5, with a saturation magnetisation of 2.26(1) μB per formula unit. These compositions display metallic behaviour, with a change in the temperature gradient of the resistivity being observed at the Curie temperature. Fe0.5Rh1.5Mo 3N is also metallic but does not show long-range magnetic order. © The Royal Society of Chemistry 2005.